2009
DOI: 10.1353/jda.0.0041
|View full text |Cite
|
Sign up to set email alerts
|

The Positive and Negative Impacts of the Sars Outbreak: A Case of the Taiwan Industries

Abstract: In this paper we employ an event study approach with GARCH process to uncover whether there were positive impacts on the Taiwan’s stock market during the SARS outbreak period in 2003. The empirical results indicate that the SARS crisis did bring negative impacts on tourism and the wholesale and retail sectors. This result has been confirmed by many previous studies, but it is most important that the biotechnology sector saw positive shocks from the impacts of the SARS crisis. It is clear that the value effect … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
1
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(59 citation statements)
references
References 24 publications
5
48
1
5
Order By: Relevance
“…Using daily data on the 1579 stocks of both Hang Seng Index and Shanghai Stock Exchange Composite Index over the COVID-19 outbreak period (from January 10 to 16 March 2020), Al-Awadhi et al (2020) highlight a negative and statistically significant relationship between stock returns and both the daily change in total confirmed cases and the daily change in total cases of death. This finding is consistent with earlier works that have examined how financial markets responded to previous epidemic diseases as the Severe Acute Respiratory Syndrome (SARS) outbreak (Chen, Jang, and Kim 2007;Chen et al 2009) and the Ebola Virus Disease (EVD) outbreak (Ichev and Marinč 2018).…”
Section: Introductionsupporting
confidence: 92%
“…Using daily data on the 1579 stocks of both Hang Seng Index and Shanghai Stock Exchange Composite Index over the COVID-19 outbreak period (from January 10 to 16 March 2020), Al-Awadhi et al (2020) highlight a negative and statistically significant relationship between stock returns and both the daily change in total confirmed cases and the daily change in total cases of death. This finding is consistent with earlier works that have examined how financial markets responded to previous epidemic diseases as the Severe Acute Respiratory Syndrome (SARS) outbreak (Chen, Jang, and Kim 2007;Chen et al 2009) and the Ebola Virus Disease (EVD) outbreak (Ichev and Marinč 2018).…”
Section: Introductionsupporting
confidence: 92%
“…The literature shows a relationship between stock market returns and pandemic outbreaks (see, inter alia, AlAli, 2020; Bash, 2020; C.-D. Chen et al, 2009;M.-H. Chen et al, 2007;Ichev & Marinč, 2018;Park et al, 2008;and Pendell & Cho, 2013). Thus, many previous studies assert that the fluctuations in stock markets because of epidemics have brought significant economic losses to stock markets (see, inter alia, Bai, 2014;Baker et al, 2012;M.-H. Chen et al, 2007;M.-P. Chen et al, 2018;Del Giudice & Paltrinieri, 2017;Delisle, 2003;Macciocchi et al, 2016;Nippani & Washer, 2004;and Wang et al, 2013).…”
Section: Introduction I Introductionmentioning
confidence: 99%
“…The results of a case-study article about Taiwan (Chen et al, 2009) indicated that SARS Coronavirus had brought about negative effects on many sectors in Taiwan including retail, wholesale and tourism.…”
Section: Literature Reviewmentioning
confidence: 99%